Foreword to Ex Novo Volume 5, 2020 - Gori, Maja; Pintucci, Alessandro; Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2021)
The fifth volume of Ex Novo has the pleasure to host Flaminia Bartolini as guest editor for the special issue titled Heritage in the Making. Dealing with Legacies of Fascist Italy and Nazi Germany. This collection of peer-reviewed papers stems in part from the successful workshop held at McDonald Institute for Archaeological Research, University of Cambridge in December 2018 under the aegis of the DAAD-Cambridge Hub. The event gathered several international heritage experts and professionals from both Germany and Italy to explore the complexities of handling Heritage related to Fascism and National Socialism.